Proteiniphilum and Methanothrix harundinacea became dominant acetate utilizers in a methanogenic reactor operated under strong ammonia stress - Feng, Gao; Zeng, Yan; Wang, Hui-Zhong; Chen, Ya-Ting; Tang, Yue-Qin (Frontiers in Microbiology, 2023)
Microorganisms in anaerobic digestion (AD) are easily affected by ammonia, especially acetoclastic methanogens. Thus, in ammonia-suppressed AD systems, acetate degradation is reported to be carried out mainly by the cooperation of syntrophic acetate oxidizers and hydrogenotrophic methanogens. Previous studies have revealed ammonia inhibition on microbial flora by AD performance, but the effect mechanism of ammonia on microbial metabolism remains poorly understood. In this study, we constructed a mesophilic chemostat fed with acetate as the sole carbon source and gradually increased the total ammonia nitrogen (TAN) concentration from 1 g L-1 to 6 g L-1. Even at the TAN of 6 g L-1, the methanogenesis kept normal, the biogas production was approximately 92% of that at TAN of 1 g L-1 and the acetate degradation ratio reached 99%, suggesting the strong TAN tolerance of the microbial community enriched. We employed the 16S rRNA gene, metagenomics, and metatranscriptomics analysis to characterize the microbial community structure and metabolic behavior. We found that the microbial community structure changed along with the TAN concentration. Methanothrix predominated in methanogens all the time, in which the dominant species was gradually replaced from M. soehngenii to M. harundinacea with the increased TAN. Dominant bacterial species also changed and Proteiniphilum showed a significant positive correlation with increased TAN. Meta-omics analysis showed that the absolute dominant microorganisms at TAN of 6 g L-1 were M. harundinacea and Proteiniphilum, both of which highly expressed genes for peroxides elimination. M. harundinacea and the second dominant methanogen Methanosarcina highly expressed both acetate cleavage and CO2 reduction pathways, indicating there were syntrophic acetate oxidizers supplying electrons or H2 to these methanogens. Proteiniphilum and some other species in Firmicutes and Synergistetes were likely acetate oxidizers in the community as they highly expressed genes for syntrophic acetate oxidization, H2 generation, and electron transfer. The results suggested that Proteiniphilum as well as M. harundinacea have strong ammonia tolerance and played critical roles in acetate degradation under ammonia-suppressed conditions. The achievements of the study would contribute to the regulation and management of the AD process.